Parental Anxiety Associated with Summer Camp Experiences: A Comparative Analysis Across Volunteer and Employee-Staffed Camps - Barry A. Garst; Ryan J. Gagnon; Lisa K-P. Olsen; Megan H. Owens (Journal of Human Sciences and Extension, 2020)
Parent anxiety can limit a parent’s willingness to involve their child in out-of-school time experiences such as summer camps. Researchers have studied anxiety within the context of camp, but these studies used narrow frameworks of anxiety. In this exploratory study, we collected open-ended responses about causes of parent anxiety associated with summer camp experiences from 656 parents whose children attended one of two Extension-administered camps. The camps represented different camp staffing models—one primarily staffed by volunteers and the other primarily staffed by employees. The primary purpose of the study was to identify salient categories of anxiety and to examine if anxiety differed based on staffing model. The secondary purpose was to develop a camp-related parent anxiety measure informed by the anxiety categories. Eleven categories were constructed from the data, which both affirmed and expanded existing literature on parent anxiety associated with camp experiences. No differences in parent anxiety were found based on staffing model, suggesting that parents were no more likely to perceive anxiety associated with camp when the program was staffed with volunteers as they were when the program was staffed by employees. Implications for practice and future directions are examined.